The Effect of Green Recruitment and Selection Practices on Organizational Sustainability Among Selected Manufacturing Firms in Ogun State, Nigeria - Tinuke Moradeke FAPOHUNDA; Kabiru Ishola GENTY; Lateef Okikiola OLANIPEKUN (Zien Journals, 2022)
This study examines the effect of green recruitment and selection practices on organisational sustainability in the Nigerian manufacturing sector with the objective of examining the effect of developing green job description on economic sustainability; examining the effect of usage of green information technology on environmental sustainability; and examining the effect of short-listing of applicants with environmental awareness on social sustainability. The study adopted a descriptive design in which questionnaires were administered for data collection. Data was collected from 155 and the hypotheses for the study were tested with regression and correlation analysis. Findings from the study illuminated that green recruitment and selection practices significantly affect organisational sustainability. The study concluded that since green recruitment and selection practices significantly affects organisational sustainability, then manufacturing Firms must uphold and incorporate these practices into their corporate agenda to promoting their sustainability. The study recommends that management of manufacturing firms should target and select applicants with green awareness and green abilities, this will help strengthen sustainability concerns and create an avenue for ensuring an eco-friendly work space.
Keywords: Economic Sustainability; Environmental Sustainability; Green Job Description; Social Sustainability